The cultural trauma of decolonization : colonial returnees in the national imagination - Eyerman, Ron.; Sciortino, Giuseppe (Switzerland: Palgrave Macmillan, 2020)
This volume is first consistent effort to systematically analyze the features and consequences of colonial repatriation in comparative terms, examining the trajectories of returnees in six former colonial countries (Belgium, France, Italy, Japan, the Netherlands, and Portugal). Each contributor examines these cases through a shared cultural sociology frame, unifying the historical and sociological analyses carried out in the collection. More particularly, the book strengthens and improves one of the most important and popular current streams of cultural sociology, that of collective trauma. Using a comparative perspective to study the trajectories of similarly traumatized groups in different countries allows for not only a thick description of the return processes, but also a thick explanation of the mechanisms and factors shaping them. Learning from these various cases of colonial returnees, the authors have been able to develop a new theoretical framework that may help cultural sociologists to explain why seemingly similar claims of collective trauma and victimhood garner respect and recognition in certain contexts, but fail in others
Includes index.
Keywords: Decolonization -- History; Decolonization in literature